Pyridoxal phosphate-dependent reactions in the biosynthesis of natural products - Du, Yi-Ling; Ryan, Katherine S (Natural product reports, 2019)
Covering: up to mid-2018 Pyridoxal 5'-phosphate (PLP) is a versatile organic cofactor used to catalyze diverse reactions on amino acid, oxoacid, and amine substrates. Here we review the reactions catalyzed by PLP-dependent enzymes, highlighting enzymes reported in the natural product biosynthetic literature. We describe enzymes that catalyze transaminations, Claisen-like condensations, and β- and γ-eliminations and substitutions, along with epimerizations, decarboxylations, and transaldolations. Finally, we describe a newly reported group of O2-, PLP-dependent enzymes. Altogether, natural product biosynthesis showcases the incredible versatility of PLP-dependent transformations for building chemical complexity.